More than Words? An Analysis on the Language and Structure of General Election Manifestos of the British Labour Party 1983-2005 - Savola, Pauliina (fi=Turun yliopisto|en=University of Turku|, 2008)
The topic of this study is the language of the educational policies of the British Labour party in the General Election manifestos between the years 1983-2005. The twenty-year period studied has been a period of significant changes in world politics, and in British politics, especially for the Labour party. The emergence educational policy as a vote-winner of the manifestos of the nineties has been noteworthy. The aim of the thesis is two-fold: to look at the structure of the political manifesto as an example of genre writing and to analyze the content utilizing the approach of critical discourse analysis. Furthermore, the aim of this study is not to pinpoint policy positions but to look at what is the image that the Labour Party creates of itself through these manifestos. The analysis of the content is done by a method of close-reading. Based on the findings, the methodology for the analysis of the content was created. This study utilized methodological triangulation which means that the material is analyzed from several methodological aspects. The aspects used in this study are ones of lexical features (collocation, coordination, euphemisms, metaphors and naming), grammatical features (thematic roles, tense, aspect, voice and modal auxiliaries) and rhetoric (Burke, Toulmin and Perelman). From the analysis of the content a generic description is built. By looking at the lexical, grammatical and rhetorical features a clear change in language of the Labour Party can be detected. This change is foreshadowed already in the 1992 manifesto but culminates in the 1997 manifesto which would lead Labour to a landslide victory in the General Election. During this twenty-year period Labour has moved away from the old commitments and into the new sphere of “something for everybody”. The pervasiveness of promotional language and market inspired vocabulary into the sphere of manifesto writing is clear. The use of the metaphors seemed to be the tool for the creation of the image of the party represented through the manifestos. A limited generic description can be constructed from the findings based on the content and structure of the manifestos: especially more generic findings such as the use of the exclusive we, the lack of certain anatomical parts of argument structure, the use of the future tense and the present progressive aspect can shed light to the description of the genre of manifesto writing. While this study is only the beginning, it proves that the combination of looking at the lexical, grammatical and rhetorical features in the study of manifestos is a promising one.